Disseminated intravascular coagulopathy in non-promyelocytic acute myeloid leukemia- incidence, clinical and laboratory features and prognostic significance - Cvetković, Mirjana; Mitrović, Mirjana (Srpski medicinski časopis Lekarske komore, 2021)
Introduction/Aim: Acute promyelocytic leukemia (APL) has the highest risk for overt disseminated intravascular coagulopathy (DIC), with reported incidence of DIC up to 90%, compared to 10-40% in other AML types. The influence of DIC on early death in non-APL AML patients is not evaluated so far. Aim of our study was to analyze of the incidence of DIC in non-APL AML, its clinical and laboratory characteristics, and impact on survival and early death of patients with non-APL AML.Methods: Total of 176 patients with non-APL AML diagnosed and treated at the Clinic of Hematology Clinical Center Serbia between 2015-2020 were evaluated retrospectively. The diagnosis of DIC was made on the basis of ISTH (International Society on Thrombosis and Haemostasis) criteria.Results:  Mean age of our patients was 53.8 ± 14.6 year, 99/176 (56.2%) were men.  DIC was present in 74/176 (42.05%) patients who had significant prevalence of hemorrhagic syndrome (p = 0.01). Risk factors for overt DIC were: older age (p
Keywords: acute myeloid leukemia; disseminated intravascular coagulopathy; outcome; survival